Why Breastfeed until Age Two?. Issue 2 (March 2023) - Spatz, Diane L.
Abstract : The American Academy of Pediatrics has recommended breastfeeding be continued until age two or more, consistent with the World Health Organization. Our breastfeeding expert, Dr. Spatz, explains the benefits and the 2022 American Academy of Pediatrics' position statement on Breastfeeding and the Use of Human Milk .